Modelo de apoio à análise decisória para a implementação de ODS em redes de empresas - Saraceni, Adriana Valélia (2018)
This thesis had as main objective the development of a model to support decision making on the implementation of Sustainable Development Goals (SDGs) in business networks mainly formed by Small and Medium Enterprises (SME). In the theoretical part of the methodological development, it was carried out the survey of the SDGs and its goals, for, through a decision matrix, aligning them to the business networks. Assuring scientific robustness to the theoretical basis of the model, a systematic review of the literature was carried out with the support of Methodi Ordinatio methodology, seeking scientific discussions about SDGs in Industrial Engineering and the fundamental variables to the model construction. Also, as a methodological procedure, to establish the structure of the model, a survey of the general indicators of implementation and monitoring was carried out, as well as of the SDG Selector tool. And aligning the theory with the general objective proposed in this research, SDG Compass was analyzed - a guide that provides guidelines for the implementation of SDGs in business strategy - in a construct of Sustainability Balanced Scorecard, in order to raise the fundamental strategies for transforming global goals into requirements and attributes of operationalization. In the mathematical part of the methodological development, the multicriteria basis was selected, based on the methodology to support the decision making MACBETH. The results of the development enabled the elaboration of an index of alignment of the SDGs target, IAM-ODSempresa, capable of supporting the decision-making process of SDGs in business networks including therefore SMEs. The empirical application was carried out in business networks in Canada and Brazil and provided results both for the calibration of the proposed model and also for the analysis of the strategic orientations of business networks in two different regional contexts. Moreover, the results of the application showed that the developed model, by providing the IAMODSempresa index of alignment of the ODS goals to the business context, supports decision-making. Thus the model offers support for effectiveness in business measures aimed at achieving the proposed UN Sustainable Development Goals for humanity.